Loss of p300 and CBP disrupts histone acetylation at the mouse Sry promoter and causes XY gonadal sex reversal - Carré, Gwenn-Aël (Hum Mol Genet, 2018)
CREB-binding protein (CBP, CREBBP, KAT3A) and its closely related paralogue p300 (EP300, KAT3B), together termed p300/CBP, are histone/lysine acetyl-transferases that control gene expression by modifying chromatin-associated proteins. Here, we report roles for both of these chromatin-modifying enzymes in mouse sex determination, the process by which the embryonic gonad develops into a testis or an ovary. By targeting gene ablation to embryonic gonadal somatic cells using an inducible Cre line, we show that gonads lacking either gene exhibit major abnormalities of XY gonad development at 14.5 dpc, including partial sex reversal. Embryos lacking three out of four functional copies of p300/Cbp exhibit complete XY gonadal sex reversal and have greatly reduced expression of the key testis-determining genes Sry and Sox9. An analysis of histone acetylation at the Sry promoter in mutant gonads at 11.5 dpc shows a reduction in levels of the positive histone mark H3K27Ac. Our data suggest a role for CBP/p300 in testis determination mediated by control of histone acetylation at the Sry locus and reveal a novel element in the epigenetic control of Sry and mammalian sex determination. They also suggest possible novel causes of human disorders of sex development (DSD).